2018
DOI: 10.13031/trans.12350
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Surface Flowpath Interception by Vegetative Buffers Using ArcGIS Hydrologic Modeling and Geospatial Analysis for Rock Creek Watershed in Central Iowa

Abstract: Abstract. Nonpoint-source (NPS) pollution is a major cause of surface water quality degradation due to the transport of chemicals, nutrients, and sediments into lakes and streams. Vegetative buffers comprise several effective landscape best management practices (BMPs) that include vegetative filter strips (VFS) and grassed waterways. However, some BMPs are less effective due to concentrated surface flow, improper cropland-to-VFS area ratios, and surface flowpaths that partially or completely bypass vegetative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The articles in this collection include modeling studies of surface drainage and BMPs, combined mole and tile drainage systems, and controlled and shallow drainage systems. Webber et al (2018) used geographic information system (GIS) hydrologic modeling functions and geospatial map comparison analysis procedures to evaluate the accuracy of simulated surface drainage flow paths relative to groundtruthed field observations. Their study showed that using a higher-resolution LiDAR digital elevation map (DEM) more accurately simulated surface flow paths than using a 30 m USGS DEM, which has typically been used for best management practice placement.…”
Section: Modelingmentioning
confidence: 99%
“…The articles in this collection include modeling studies of surface drainage and BMPs, combined mole and tile drainage systems, and controlled and shallow drainage systems. Webber et al (2018) used geographic information system (GIS) hydrologic modeling functions and geospatial map comparison analysis procedures to evaluate the accuracy of simulated surface drainage flow paths relative to groundtruthed field observations. Their study showed that using a higher-resolution LiDAR digital elevation map (DEM) more accurately simulated surface flow paths than using a 30 m USGS DEM, which has typically been used for best management practice placement.…”
Section: Modelingmentioning
confidence: 99%